YARÍMÓTKIZGISHLERDIŃ TIYKARǴÍ PARAMETRLERINIŃ BASÍM TÁSIRINDE ÓZGERIWI - Tursınbaev, S.A.; Tajetdinova, M.O.; Oteulieva, Yu.M. (SCIENCE and SOCIETY, 2025)
This article studies the strain-sensitive properties of semiconductors and their changes in the doped state with impurity atoms. The study examines the influence of external factors such as pressure, temperature and mechanical deformation on the electrophysical parameters and strain-sensitive properties of silicon materials. In particular, it shows the change in the physical parameters such as electrical resistance, magnetic resistance and thermal conductivity of silicon and samples doped with dopant atoms depending on pressure. The study of these properties is of great scientific and practical importance for the creation of new semiconductor materials and sensors. The results of the study are an important step in the development of highly sensitive sensors in the field of micro- and nanoelectronics.